The knockout of Moesin leads to excess microglia-mediated synaptic pruning and impairs social novelty in a mouse model - Wanjing Lai; Junlin Chen; Hongyao Zhu; Yunbo Jiang; Yimei Niu; Qingpei Chen; Zhihua Luo; Yu Hu; Li Fang; Yaxuan Wang; Youqiang Song; Charlly Kao; et al. (Cell Reports, 2025)
Summary: Genome-wide association studies (GWASs) have implicated a noncoding antisense RNA designated as MSNP1AS (Moesin pseudogene 1, antisense) in susceptibility to autism spectrum disorders (ASDs). MSNP1AS binds to and downregulates the Moesin (Msn) transcript and is highly overexpressed in the postmortem cerebral cortex of individuals with ASDs. However, the mechanistic link between Msn loss in vivo and ASD-related phenotypic traits remains enigmatic. Here, we generate Msn knockout (KO) mice, on which neurobehavioral tests reveal impaired social novelty and repetitive behaviors. Msn KO activates the microglial population, leading to aberrant C1q-dependent synaptic pruning followed by synaptic deficits in the medial prefrontal cortex. The aberrant regulatory pathway can be rescued by IFNAR1 antibody, which rescues microglial abnormalities and social deficits. Taken together, the results of the current study reveal a pathway in which Msn mediates interferon signaling and synaptic pruning to affect ASD-like behaviors, providing a functional genetic link between MSN and neurobehavioral abnormalities.